Kualitas Produk dan Harga Jual terhadap Kepuasan Konsumen - Titi Hasanah; Markus Markus; M Pahlan; Rudy Eduar; Nidyawati Nidyawati (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of product quality and selling price independently or jointly on consumer satisfaction (a case study in Bipang Tanjung Sakti). This research method is descriptive quantitative. The sample in this study were 67 Bipang Tanjung Sakti consumers taken based on a portion of the population to represent the entire population using the Slovin formula calculation with a confidence level of 90% and an error rate of 10% (0.1). Sampling using accidental sampling method. The results showed, a) the product quality variable (X1) on consumer satisfaction (Y), obtained a Sig value of 0.000 <0.05; b) the selling price variable (X2) on consumer satisfaction (Y), obtained a value of Sig 0.000 <0.05; c) variable product quality (X1) and selling price (X2) together on consumer satisfaction (Y), obtained Sig value, 0.000 <0.05. In conclusion, product quality variables have a significant effect on consumer satisfaction variables, selling price variables have a significant effect on consumer satisfaction variables, product quality variables, and selling prices, have a significant effect on consumer satisfaction variables together. Keywords: Selling Price, Consumer Satisfaction, Product Quality